The long run evolution of inequality and macroeconomic shocks - Morelli, S (2013)
This thesis is concerned with two main questions. Do systemic banking crises substantially affect the income distribution in a country? Is income inequality a destabilising factor for the macro-economy? In order to answer the first question, this thesis examines a panel of 26 countries since 1900 and assembles a new database of crises, finding that the impact of major banking crises on the national income shares detained by the income groups within the richest decile is mostly small in magnitude. Indeed, the estimated impact is never bigger than a standard deviation of the specific top shares under investigation. Results are also confirmed in a separate analysis for the United States and are robust to a series of checks. These findings lend indirect support to the structuralist hypothesis that only substantial changes in government policies and institutional frameworks can bring about radical changes in income distribution. The analysis also highlights interesting heterogeneity across different income groups, country groups and time periods. The second question is addressed by making use of a newly assembled database on different dimensions of economic inequality. The new data helps to reject the statistical validity of the hypotheses that either growing inequality or a high level of inequality may systematically precede the onset of major banking crises. In addition, simulations based on the UK Family Expenditure Survey data find that even a full equalisation of income would increase the aggregate consumption by 3 percentage points at most. These findings, taken together, point out that an increase in income inequality may not concur to reduce the pressure on aggregate demand or be adduced as a structural factor of financial instability. Nonetheless, the evidence is not yet clear cut as the work further documents that periods of increasing income inequality in the UK were also associated with a reduction of the saving rates across the whole income distribution since 1968. The analysis contends that such evidence of under-saving behaviour may be consistent with the relative income hypothesis and some of its recent formulations such as the ’expenditure cascades’ theory.